Knights of the Zodiac [videorecording (DVD)] - Campbell, Josh; Stuecken, Matt; Murray, Kiel; Mackenyu; Janssen, Famke, 1964-; Iseman, Madison, 1997-; Tinoco, Diego; Dacascos, Mark, 1964-; Stahl, Nick, 1979-; Bean, Sean; Kurumada, Masami (Sony Pictures Home Entertainment, 2023)
Seiya, a headstrong street teen, spends his time fighting for cash while he searches for his abducted sister. When one of his fights unwittingly taps into mystical powers he never knew he had, Seiya finds himself thrust into a world of warring saints, ancient magical training, and a reincarnated goddess who needs his protection. If he's to survive, he will need to embrace his destiny and sacrifice everything to take his rightful place among the Knights of the Zodiac.